2005
DOI: 10.1016/j.cub.2005.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functions of the Tribolium zerknu¨llt Genes in Serosa Specification and Dorsal Closure

Abstract: In Tribolium, the duplication of the zen genes was accompanied by subfunctionalization. One of the paralogues, Tc-zen1, acts as an early anterior-posterior patterning gene by specifying the serosa. In absence of the serosa, Tribolium embryogenesis acquires features of long-germ development with a single extraembryonic membrane. We discuss implications for the evolution of insect development including the origin of the zen-derived anterior determinant bicoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(189 citation statements)
references
References 44 publications
6
179
2
2
Order By: Relevance
“…4) as found in other insects, and in the CNS in late honey bee embryos. CNS expression is not reported for zen genes in Tribolium (Falciani et al 1996;van der Zee et al 2005), Diptera (Doyle et al 1989), or Schistocerca (Dearden et al 2000), implying a novel function in the honey bee. The second rogue Hox gene, fushi tarazu (ftz), acts in Drosophila in segmentation and nervous system patterning.…”
Section: The Hox Complexmentioning
confidence: 89%
“…4) as found in other insects, and in the CNS in late honey bee embryos. CNS expression is not reported for zen genes in Tribolium (Falciani et al 1996;van der Zee et al 2005), Diptera (Doyle et al 1989), or Schistocerca (Dearden et al 2000), implying a novel function in the honey bee. The second rogue Hox gene, fushi tarazu (ftz), acts in Drosophila in segmentation and nervous system patterning.…”
Section: The Hox Complexmentioning
confidence: 89%
“…Indeed, immune gene expression was shown to be restricted to the extraembryonic regions of the egg in Manduca sexta (Gorman et al, 2004). By using RNAi to prevent the development of the serosa (van der Zee et al, 2005), we were able to show that the endogenous innate immune response of the Tribolium castaneum egg is completely dependent on the extraembryonic serosa (Jacobs et al, 2014a;. Immune gene activity in insect eggs is not only activated by a pathogen attack, but it can also be enhanced by parental immune priming.…”
Section: Introductionmentioning
confidence: 93%
“…In Drosophila, zen is dorsally expressed during blastoderm development and is required for development of the amnioserosa (Wakimoto et al, 1984;Doyle et al, 1986). zen is also expressed in the anterior and dorsal regions that give rise to extraembryonic membranes in other insects (Falciani et al, 1996;Stauber et al, 2002); in Tribolium, anterior expression of zen1 has also been shown to specify serosa cell fates, differentiating them from those of the more posterior germ rudiment (van der Zee et al, 2005). Nasonia Hunchback is also strongly expressed in the nervous system, approximately during the period of head involution, in a pattern that appears to be similar to that observed in the nervous system of other insects (Woff et al, 1995;Rohr et al, 1999;Patel et al, 2001).…”
Section: Comparative Timing and Expression Of Nasonia And Drosophila mentioning
confidence: 99%